Innovative Solid Lipid Nanoparticle-Enriched Hydrogels for Enhanced Topical Delivery of L-Glutathione: A Novel Approach to Anti-Ageing - Mengyang Liu; Manisha Sharma; Guoliang Lu; Zhiwen Zhang; Wenting Song; Jingyuan Wen (Pharmaceutics)
Background: Skin ageing, driven predominantly by oxidative stress from reactive oxygen species (ROS) induced by environmental factors like ultraviolet A (UVA) radiation, accounts for approximately 80% of extrinsic skin damage. L-glutathione (GSH), a potent antioxidant, holds promise in combating UVA-induced oxidative stress. However, its instability and limited penetration through the stratum corneum hinder its topical application. This study introduces a novel solid lipid nanoparticle (SLN)-enriched hydrogel designed to enhance GSH stability, skin penetration, and sustained release for anti-ageing applications. Methods: GSH-loaded SLNs were prepared via a double-emulsion technique and optimized using factorial design. These SLNs were incorporated into 1–3% (w/v) Carbopol hydrogels to produce a semi-solid formulation. The hydrogel’s characteristics, including morphology, mechanical and rheological properties, drug release, stability, antioxidant activity, cytotoxicity, and skin penetration, were evaluated. Results: SEM and FTIR confirmed the uniform dispersion of SLNs within the hydrogel. The formulation exhibited desirable properties, including gel strength (5.1 ± 0.5 g), spreadability (33.6 ± 1.9 g·s), pseudoplasticity, and elasticity. In vitro studies revealed a biphasic GSH release profile, with sustained release over 72 h and over 70% cumulative release. The hydrogel significantly improved antioxidant capacity, protecting human fibroblasts from UVA-induced oxidative stress and enhancing cell viability. Stability studies indicated that 4 °C was optimal for storage over three months. Notably, the hydrogel enhanced GSH penetration through the stratum corneum by 3.7-fold. Conclusions: This SLN-enriched hydrogel effectively improves GSH topical delivery and antioxidant efficacy, providing a promising platform for anti-ageing and other bioactive compounds with similar delivery challenges.